Molecular Evaluation of rfbE Gene Expression Changes under Different Creatinine Concentrations in Escherichia coli Strains Via Real-Time PCR - Janbakhsh, E.; Mehrabi, M.R.; Джанбахш, Е.; Мехрабі, М.Р. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
Background and objective. Escherichia coli (E. coli) O157: H7 as an enterohemorrhagic pathogen causes severe damage to the gastrointestinal tract and dangerous diseases in humans such as hemolytic uremic syndrome (HUS) and acute renal failure, which is associated with increased blood creatinine levels. This study aimed to evaluate antibiotic resistance of E. coli O157: H7 pathotypes to detect the virulence of gene rfbE and to study variations in its expression. Methods. The isolates were first inoculated on eosin methylene blue (EMB) agar and then identified using the Microgen kit and the presence of rfbE gene. Antibiotic susceptibility of the identified strains was tested by the disk diffusion technique, followed by inoculating E. coli O157: H7 strains at concentrations of 1, 3, and 6 mg dl–1 in BHI broth. DNA and RNA were then extracted from the bacteria, and cDNA was prepared from purified RNA. Then, the rfbE gene expression was evaluated using a real-time PCR approach, and the data were analysed with Rest software. Results. The research results revealed high resistance of isolated strains against some of the studied antibiotics, and variations in the expression of the rfbE gene were found to be different at different creatinine concentrations and at different time points. A significant decrease in variations in the rfbE gene expression was observed at low concentrations (1 mg dl-1), but, on the contrary, a significant increase in variations in the rfbE gene expression was found at higher concentrations (3 and 6 mg dl-1) (p<0.05). Conclusions. The rfbE gene is one of the factors affecting the bacterial virulence. We believe that a secondary increase in creatinine for any reason can exacerbate kidney disease and failure by affecting the rfbE gene expression while producing O antigen or bacterial endotoxin.